2004
DOI: 10.1016/s0002-9440(10)63309-3
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Deletion of CC Chemokine Receptor 2 Attenuates Left Ventricular Remodeling after Experimental Myocardial Infarction

Abstract: A key component of cardiac remodeling after acute myocardial infarction (MI) is the inflammatory response, which modulates cardiac tissue repair. The purpose of this study was to investigate the relationship between the monocytic inflammatory response and left ventricular remodeling after MI using mice deficient in CC chemokine receptor 2 (CCR2), the primary receptor for the critical regulator of CC chemokine ligand 2. Immunohistochemical analysis revealed rapid infiltration of macrophages into infarcted tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
150
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(167 citation statements)
references
References 43 publications
(38 reference statements)
16
150
1
Order By: Relevance
“…Data are expressed as mean ± SEM. Further, in our current study, we did not observe an altered progression toward heart failure in CCR2KO BMT mice, which, coupled with the positive outcome of CCR2 inhibition in the aforementioned studies (25,26) versus the catastrophic impact of immune cell-specific β2AR deletion on cardiac remodeling following MI we previously reported (7), suggests that β2ARKO chimeric mice likely have additional factors that contribute to their observed post-MI phenotype. For instance, we previously showed that enhanced vascular cell adhesion molecule 1 expression was associated with splenic retention of leukocytes in β2ARKO BMT mice and that splenectomy partially restored cardiac leukocyte infiltration following MI (7), demonstrating that even with diminished CCR2 expression and responsiveness, β2AR-deficient leukocytes retain some capacity to traffic to sites of injury in vivo.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Data are expressed as mean ± SEM. Further, in our current study, we did not observe an altered progression toward heart failure in CCR2KO BMT mice, which, coupled with the positive outcome of CCR2 inhibition in the aforementioned studies (25,26) versus the catastrophic impact of immune cell-specific β2AR deletion on cardiac remodeling following MI we previously reported (7), suggests that β2ARKO chimeric mice likely have additional factors that contribute to their observed post-MI phenotype. For instance, we previously showed that enhanced vascular cell adhesion molecule 1 expression was associated with splenic retention of leukocytes in β2ARKO BMT mice and that splenectomy partially restored cardiac leukocyte infiltration following MI (7), demonstrating that even with diminished CCR2 expression and responsiveness, β2AR-deficient leukocytes retain some capacity to traffic to sites of injury in vivo.…”
Section: Discussionsupporting
confidence: 77%
“…These discrepancies may be a result of the timing of administration or inhibition, because short-term elevations in CCL2 are protective whereas sustained elevations in CCL2 contribute to an enhanced progression toward heart failure (21)(22)(23)(24). Indeed, studies examining the involvement of CCR2 following cardiac injury have shown beneficial effects with CCR2 inhibition (25)(26)(27), wherein both global and monocyte-directed RNAi-mediated deletion of CCR2 in mice that underwent MI surgery resulted in improved left ventricular remodeling (25,26). CCR2 is highly expressed on proinflammatory monocyte populations and, although β2AR has been shown to modulate chemotaxis, our findings are novel in that they directly link decreased hematopoietic cell β2AR expression with a corresponding reduction in CCR2 levels and CCL2-dependent migration.…”
Section: Discussionmentioning
confidence: 99%
“…Markedly increased thrombus collagen was observed in the CCR2 Ϫ/Ϫ mice at early time points and at 4 days was associated with reduced vein wall levels of MMP-2 and MMP-9, suggesting impaired collagenolysis. This observation has also been described in a model of pulmonary and cardiac fibrosis in CCR2 Ϫ/Ϫ mice, showing significantly reduced MMP-2 and MMP-9 activity (11,47). Although MMP-9 has collagenolytic activity, it is primarily against type I collagen, for which little was present in the thrombus.…”
Section: Discussionsupporting
confidence: 70%
“…The observations that macrophage depletion results in delayed cardiac repair and worsened outcomes after MI (3), whereas inhibition of monocyte recruitment to the heart improves outcomes after MI (22), have long been viewed as contradictory. In light of our recent understanding of macrophages ontology, it may now be possible to reconcile these seemingly contradictory findings.…”
Section: Inhibition Of Monocyte Recruitment Preserves Embryonic-derivedmentioning
confidence: 99%